The anxiety book developing strength in the face of fear - Davidson, Jonathan R. T. 1943-; Dreher, Henry (New York Riverhead Books, 2004)
The Anxiety book is a comprehensive resource for defeating anxiety and building resilience. Dr. Davidson includes: questionnaires to help you find out which type of anxiety you have; information on the most effective treatments for each form of anxiety-from cognitive techniques to state-of-the-art medication; a five-point plan for recovery through relaxation, changing the way you think, diet, exercise, and herbs and medications; case studies from Dr. Davidson's extensive research and medical practice and a comprehensive medication chart to inform the reader of efficacy, dosage, and side effects of the most commonly used drugs, as well as those that have barely hit the market. Backed by peer-reviewed research and twenty-five years of clinical experience, Dr. Davidson brings solid methods and reassuring advice to the millions who suffer in silence.
1. Anxious? : you're not alone -- 2. The five faces of anxiety : which one is mine -- 3. Solution 1 : change your fearful beliefs -- 4. Solution 2 : vaccinate your anxious mind : exposure therapy -- 5. Solution 3 : developing serenity skills -- 6. Solution 4 : medications -- 7. Solution 5 : diet, exercise, and herbs -- 8. Resilience : life beyond anxiety.
Includes bibliographical references (pages [284]-294) and index.
Keywords: Anxiety; Anxiety -- Case studies